The Characteristics of Polymer Concrete Reinforced with Polypropylene Fibres Under Axial and Lateral Compression Loads - Azman N.A.; Syamsir A.; Bakar M.S.A.; Rizal M.A.M.; Sanusi K.A.; Abdullah M.J. (Universiti Putra Malaysia Press, 2024)
The use of cement is expected to increase over the years as the infrastructure continues to develop, and the needs to repair or rehabilitate an old and deteriorated building are necessary. However, many investigations have been conducted to establish promising polymer concrete applications in the last few decades. Meanwhile, using concrete in the construction industry has led to environmental issues. It is because relying on cement production in concrete will contribute to about 7% of the worlds carbon dioxide emissions. Therefore, polymer concrete was introduced in this study to minimise the use of cement in the industry. This research investigated the influence of different amounts of polypropylene (PP) fibre content on polymer concrete (PC) properties by determining the compressive strength, flexural strength and indirect tensile strength. Furthermore, the results of PC failure characteristics have been discussed. The polymer concrete specimens in this study have been cast into cylinders and prismatic specimens using PVC pipe and plywood formwork to determine the compressive strength, splitting tensile strength and flexural strength. By reinforcing PP fibre in the polymer concrete with a specific percentage of fibre reinforced, the overall strength of the polymer concrete was improved. Based on the compressive, splitting tensile, and flexural test results, it has been hypothesised that the 0.16% PP fibre will considerably improve polymer concrete. Additionally, PP fibre maintains a moisture content of less than 0.5% in the aggregates, resulting in a significant enhancement in the mechanical properties of polymer concrete. Universiti Putra Malaysia Press.